(untitled) - Johnstone, Barbara (Malden, MA, 2008)
Fully revised and updated throughout, the new edition of Discourse Analysis is a user-friendly textbook for students taking their first course in linguistic approaches to discourse.
Keywords: Discourse analysis,Phân tích thuyết trình